Effect of ring rotation upon gas adsorption in SIFSIX-3-M (M = Fe, Ni) pillared square grid networks. Issue 3 (10th January 2017) - Elsaidi, Sameh K.; Mohamed, Mona H.; Simon, Cory M.; Braun, Efrem; Pham, Tony; Forrest, Katherine A.; Xu, Wenqian; Banerjee, Debasis; Space, Brian; Zaworotko, Michael J.; Thallapally, Praveen K.
Abstract : Dynamic and flexible metal–organic frameworks (MOFs) that respond to external stimuli, such as stress, light, heat, and the presence of guest molecules, hold promise for applications in chemical sensing, drug delivery, gas separations, and catalysis. Abstract : Dynamic and flexible metal–organic frameworks (MOFs) that respond to external stimuli, such as stress, light, heat, and the presence of guest molecules, hold promise for applications in chemical sensing, drug delivery, gas separations, and catalysis. A greater understanding of the relationship between flexible constituents in MOFs and gas adsorption may enable the rational design of MOFs with dynamic moieties and stimuli-responsive behavior. Here, we detail the effect of subtle structural changes upon the gas sorption behavior of two "SIFSIX" pillared square grid frameworks, namely SIFSIX-3-M (M = Ni, Fe). We observe a pronounced inflection in the Xe adsorption isotherm in the Ni variant. With evidence from X-ray diffraction studies, density functional theory, and molecular simulations, we attribute the inflection to a disordered to ordered transition of the rotational configurations of the pyrazine rings induced by sorbate–sorbent interactions. We also address the effect of cage size, temperature, and sorbate on the guest-induced ring rotation and the adsorption isotherms. The absence of an inflection in the Xe adsorption isotherm in SIFSIX-3-Fe and in the Kr, N2, and CO2 adsorption isotherms in SIFSIX-3-Ni suggest that the inflection is highly sensitive to the match between the size of the cage and the guest molecule.